Analisis beban kerja room attendant di asialink hotel kota Batam - Okki Kurnia; Nensi Lapotulo; Devid Trinaldo Simatupang; Nofita Nanda Hermawati (STIE Pariwisata API Yogyakarta, 2023)
The purpose of this study is to find out how the workload of room attendants at Asialink Hotel Batam City, based on the Koesomowidjojo workload theory with 3 indicators (work conditions, use of working time, targets to be achieved). This research is a qualitative descriptive study with the object of research are room attendants and participants from the Department of Housekeeping. The results of this study indicate that the workload on the employees of the Housekeeping Department, especially room attendants, is not optimal enough. The existence of multi-profession work, namely employees get workload from two types of work as room attendants and public area attendants, causing a lack of work focus on employees and having an impact on employee work mobility in one or both of the work professions carried. Management can provide work professions to employees separately, this can be done by increasing the number of workers in the Housekeeping Department.